An update: circulating tumor cells in head and neck cancer. (2nd December 2019) - Kulasinghe, Arutha; Hughes, Brett G.M.; Kenny, Liz; Punyadeera, Chamindie
ABSTRACT: Introduction : Local and distant metastatic disease occurs in approximately half of head and neck squamous cell carcinoma (HNSCC) patients, representing an ongoing cause for treatment failure. Circulating tumor cells (CTCs) are transient cancer cells which have the capacity to metastasize to distant sites such as the lungs and liver in HNSCC. When metastatic disease is radiographically evident, the patient prognosis is often poor. Therefore, methodologies to assess micrometastatic disease are needed to (1) identify patients likely to develop metastatic disease and (2) treat and monitor these patients more aggressively. Whilst CTCs are well documented in other tumor streams such as breast, colorectal cancer and prostate cancers, the data and clinical utility in HNSCC remains limited. Areas covered : Here we summarize the recent advances of CTCs and applications in HNSCC. Expert opinion : CTC enumeration can be prognostic in HNSCC; further studies are warranted to investigate the role of CTC clusters in HNSCC; CTC culture ( in vivo / ex vivo ) may present a possibility to expand these rare cells to a critical mass for functional testing; PD-L1 expression of HNSCC CTCs may present a means by which to determine patients likely to respond to therapy; a HNSCC CTC-specific marker is warranted.